TEORI BELAJAR SEBAGAI LANDASAN BAGI PENGEMBANGAN TEKNOLOGI PENDIDIKAN - Sinaga, Marsaulina Nirmaisi; Ringo, Samuel Siringo; Netrallia, Mei Ceria (Penerbit Widina, Widina Media Utama, 2024)
In the development of educational technology, learning theories play a crucial role as a foundation for designing effective learning experiences. This article examines the significance of learning theories as a basis for the development of educational technology. The research aims to analyze the role of learning theories in the development of educational technology and to identify the relationship between learning theories and educational technology. The study employs a literature analysis method by gathering and analyzing various relevant scholarly references on learning theories and the development of educational technology. The results of the research demonstrate that learning theories have a highly important role in designing effective educational technology. Learning theories, such as behaviorism, constructivism, and social constructivism, provide a useful framework for creating learning experiences tailored to the needs of individuals and groups. This article concludes that a strong understanding of learning theories is crucial in the development of successful educational technology. By leveraging the principles of learning theories, we can design more effective and relevant educational solutions for the future. ABSTRAKDalam pengembangan teknologi pendidikan, teori belajar memainkan peran kunci sebagai dasar untuk merancang pengalaman belajar yang efektif. Artikel ini mengkaji pentingnya teori belajar sebagai landasan bagi pengembangan teknologi pendidikan. Penelitian ini bertujuan untuk menganalisis peran teori belajar dalam pengembangan teknologi pendidikan dan untuk mengidentifikasi hubungan antara teori belajar dan teknologi pendidikan. Penelitian ini menggunakan metode analisis literatur dengan mengumpulkan dan menganalisis berbagai referensi ilmiah yang relevan tentang teori belajar dan pengembangan teknologi Pendidikan 10 tahun terakhir. Hasil penelitian menunjukkan bahwa teori belajar memiliki peran yang sangat penting dalam merancang teknologi pendidikan yang efektif. Teori-teori belajar, seperti behaviorisme, konstruktivisme, dan konstruktivisme sosial, memberikan kerangka kerja yang berguna untuk merancang pengalaman belajar yang sesuai dengan kebutuhan individu dan kelompok. Artikel ini menyimpulkan bahwa pemahaman yang kuat tentang teori belajar sangat penting dalam pengembangan teknologi pendidikan yang berhasil.